The Effects of Propolis Extract to Cellular Immune System of Rattus Norvegicus Strain Wistar - Radiati, Lilik Eka; Al Awwaly, Khotibul Umam; Kalsum, Ummi; Jaya, Firman (Jurnal Teknologi Pertanian, 2008)
An experiment type of research was conducted to find out the effects of propolis extract dosage on the cellular immune system of Rattus norvegicus. The administration per oral of propolis extract was 40 days and given at different  levels of dosage for each group :  9 mg/day (1st group); 12 mg/day (2nd group) and 15 mg/day (3rd group). The results showed that the average level of leucocytes in the control group    (untreated one) was 3883,33 ± 1563,86 cell/mm3, which comprised of 75,17 ± 4,36 % lymphocytes,  6,67 ± 2,66 % monocytes and 18,17 ± 5,12 % granulocyte. The average level of leucocytes of the first group was 3616,67 ± 1085,20 cell/ mm3 (contained 75,67 ± 4,50 % lymphocytes, 10,50 ± 5,21 % monocytes and 13,83 ± 2,14 % granulocytes);  The second one was 4100 ± 551,36 cell/ mm3 leucocytes (containing 67,33 ± 8,57 % lymphocytes, 3,50 ± 1,38 % monocytes and 25 ± 5,48 % granulocytes), and the third one was 4383,33 ± 1121,46 cell/ mm3 which contained 70 ± 5,10 % lymphocytes, 1,83 ± 0,41 % monocytes and 28,17 ± 5,19 % granulocytes. It may be concluded that the propolis extract could increase the number of leucocytes that influential to response cellular immune system of Rattus norvegicus. The increase of propolis dosage concentration significantly not related each other because the lymphocytes and monocytes cell have a similar correlation.Key words: propolis extract, leucocytes, cellular immune system